TI_GERICHTE 72.2017.124 vom 22. März 2018 , Infrazione grave alle norme della circolazione stradale, eccesso di velocità - TI Tribunale d'appello (2018)
Infrazione grave alle norme della circolazione stradale, eccesso di velocità